2012
DOI: 10.1002/ajim.22146
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Chemical Exposures in Nail Salons through Owner and Worker Trainings: An Exploratory Intervention Study

Abstract: Worker education disseminated through salon owners to their workers can improve work-related knowledge, behavior, health symptoms, and exposures for select air contaminants, although more research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 26 publications
4
40
1
Order By: Relevance
“…A recent pilot study has demonstrated that education on workplace chemical exposure through salon owners to their employees can significantly increase work-related knowledge, safety behavior, health symptoms, and exposures to toxic chemicals in Vietnamese salon workers. 21 In our study, nearly 90% of the participants indicated interest to learn more about safe work practices. Both hardcopy materials (eg, brochures) and electronic materials (eg, Internet sites) were preferred by 57% and 51% of the respondents as sources of information.…”
Section: Commentmentioning
confidence: 59%
See 1 more Smart Citation
“…A recent pilot study has demonstrated that education on workplace chemical exposure through salon owners to their employees can significantly increase work-related knowledge, safety behavior, health symptoms, and exposures to toxic chemicals in Vietnamese salon workers. 21 In our study, nearly 90% of the participants indicated interest to learn more about safe work practices. Both hardcopy materials (eg, brochures) and electronic materials (eg, Internet sites) were preferred by 57% and 51% of the respondents as sources of information.…”
Section: Commentmentioning
confidence: 59%
“…It is also evident in a recent study that to reduce chemical exposure in nail salons interventions should target both owners, who are also the decision-makers, and workers to promote positive health behavior. 21 The present study will provide useful information to salon owners, and their advocates, to develop training strategies and improve practices within their workplaces.…”
Section: Commentmentioning
confidence: 96%
“…Several of these VOCs have known or suspected adverse effects, including: irritation to eye, skin and nose; damage to the respiratory system, liver and kidney; reproductive effects; and breast cancer. Several studies have indicated potentially harmful exposure levels (Alaves et al 2013; Quach et al 2011; Quach et al 2008; Quach et al 2013; Roelofs et al 2008; Roelofs and Do 2012; Tsigonia et al 2010), e.g., formaldehyde levels exceeded the National Institute for Occupational Safety and Health recommended exposure limits (NIOSH RELs) in 58% of samples collected in a California study (Alaves et al 2013). Adverse health effects observed among NSTs include asthma, dermatitis, and neurological symptoms (Quach et al 2014; Roelofs et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We examine conditions in 17 nail salons in two seasons, and identify the composition of chemicals currently in use. We investigate occupational inhalation exposures among Michigan NSTs, an unstudied cohort; explore whether VOC concentrations are amplified due to the lower ventilation rates expected in Michigan, especially in winter, as compared to the California studies (Alaves et al 2013; Quach et al 2008; Quach et al 2013); use quasi-personal breathing zone measurements to better reflect exposure than the area measurements used in most previous studies; and take repeated measurements to examine variability over time and across salons, which has not been reported in previous studies. Lastly, the study is unique in measuring the composition of 35 common products used by NSTs and using this “fingerprint” information to identify emission sources that contribute to VOC exposure, providing key information needed to formulate practical control measures.…”
Section: Introductionmentioning
confidence: 99%
“…Discrepancies between certain topics specific to each state may also be addressed with an expanded focus on those particular subject areas and others of emerging concern in hair and nail salons. [22][23][24] For example, in NJ, the topic area of the Brazilian hair treatments and the harmful chemicals associated with such products, and in GA, the topics of blood borne pathogens and associated infections. More data will help determine if those differences were from variations in learning techniques between training JCHAS 765 [1][2][3][4][5][6][7][8][9] Please cite this article in press as: Apostolico, A., et al, The ''Salon Safety Quiz'' for pre-/post-evaluation assessment when training young cosmetology workers in public secondary schools, J. Chem.…”
Section: Discussionmentioning
confidence: 99%